Weaving Ideas: A Proposal for the Strategic Teaching of the Use of Connectors in Academic Essays - Alonso Chacón, Paula (2012)
This essay has two purposes. The first one is to show the ups and downs of discourse, presented by freshmen from the Centre for General Studies (CEG) at “Universidad Nacional” in the use of discourse connectors in academic papers as a consequence of the grammatical teaching of the mother tongue. The second one is to share the design of a didactically oriented strategic teaching of this language resource in order to diminish the discursive gaps surrounding textual cohesion in writing courses at the higher education level. These purposes are some of the results from a Final Graduation Project from the Master's Degree Program in Education with an emphasis on University Level Teaching from “Universidad Nacional.”